Design criteria for educational buildings in the state of Zulia, Venezuela - Portillo Ríos, Raymundo (Corporación Universitaria del Caribe, CECAR., 2016)
Abstract: This work seeks to determine the design criteria for the buildings of the public educational units of the state of Zulia. For this, a holistic, descriptive research was proposed with a qualitative approach, with descriptive documentary design and multi-variable trait (eventual). Public educational institutions bring together the largest number of children and young people enrolled in the Venezuelan school system, with Zulia being the region with the highest school enrollment. Thus, the main beneficiaries of this study are the agencies responsible for implementing public policies in terms of school infrastructure, as well as the communities served with such spaces. The analysis procedure was qualitative, with the intention of categorizing the data of the sources used. They were made following the formal, spatial, functional, environmental aspects and the constructive technique of the buildings studied. From this perspective, the general design criteria for the public educational buildings of the region, framed in the current FEDE regulations, are listed. ___Keywords: Design criteria, educational buildings, school architecture, public schools. ___Resumen: Este trabajo busca determinar los criterios de diseño para las edificaciones de las unidades educativas públicas del estado Zulia. Para ello, se planteó una investigación holística, descriptiva con enfoque cualitativo, con diseño descriptivo documental y multi-variable de rasgo (eventual). Las instituciones educativas públicas agrupan la mayor cantidad de niños y jóvenes inscritos en el sistema escolar venezolano, siendo el estado Zulia la región con la mayor cantidad de matrícula escolar. De tal manera, que los principales beneficiarios de este estudio son los organismos encargados de ejecutar las políticas públicas en términos de infraestructura escolar, así como también las comunidades servidas con dichos espacios. El procedimiento de análisis fue cualitativo, con la intención de categorizar los datos de las fuentes utilizadas. Los mismos se hicieron siguiendo los aspectos formales, espaciales, funcionales, ambientales y la técnica constructiva de las edificaciones estudiadas. Desde esta perspectiva, se enumeran los criterios generales de diseño para las edificaciones educativas públicas de la región, enmarcados en la normativa vigente de FEDE. ___Palabras clave: Criterios de diseño, edificaciones educativas, arquitectura escolar, escuelas públicas. ___Recibido: 2 de mayo 2016. Aceptado: 23de julio 2016.